EVALUASI PELAKSANAAN KEBIJAKAN PERATURAN DAERAH INDRAGIRI HULU NOMOR 3 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (STUDI KASUS MAGHRIB MENGAJI KEBIJAKAN KOTA LAYAK ANAK DI DESA AIR MOLEK II KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU) - Putri Nuraplina; Herman Herman (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The purpose of this research is to find out the evaluation of the implementation of regional regulation No. 3 Year 2014, which concerning on children protection (Case study ofMagrhribMengaji, the policy of proper city for children in sub-district of Air Molek II, PasirPenyu district, Indragiri Hulu regency). The evaluation is measuredby using four indicators, which are communication, resources, disposition, and bureaucracy structure. The hypothesis of this study is how is the evaluation of the implementation of regional regulation No. 3 Year 2014, which is about children protection (Case study ofMagrhribMengaji, the policy of proper city for children in sub-district of Air Molek II, PasirPenyu district, IndragiriHulu regency)? This is descriptive study, which is conducted through survey. This study is located in Department of Women`s Empowerment and Child Protection in Indragiri Hulu regency, the district office of PasirPenyu, head of sub-district office of Air Molek II and sub-district of AirMolek II. The population of this study are Head of Fulfillment for Children Rights, Head of PasirPenyu district, Head of Air Molek II sub-district, and 514 people of Air Molek II sub-district while the sample of this study consists of 53 people. The data that is usedare primer data, which is gotten from questioner and interview and secondary data like documentation. The result of this study can be concluded that generally, the evaluation of the implementation of regional regulation No. 3 Year 2014, which concerning on children protection (case study ofMagrhribMengaji, the policy of proper city for children in sub-district of Air Molek II, PasirPenyu district, IndragiriHulu regency) is fair enough. However, there are obstaclesin this activity, which are lack participation of the society or the parents to assign their children to join with the activity of MaghribMengaji, lack of government policy that regulates the procedure of MaghribMengaji, and lack of teaching staff so that it makes the participants becomes less discipline